The effect of audit committee characteristics and auditor changes on financial restatement in Iran - Mahdi Salehi; Mahdi Mokhtarzadeh; Mohammad Sadegh Adibian (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
The present study aims to realize and become more familiar with the impact and the functions of audit committee and its characteristics, including the expertise and independence of members, related experiences, and change of auditor on the quality of financial reporting in companies listed on the Tehran Stock Exchange (TSE). The required data are gathered from 105 listed companies on the TSE during 2012-2016 and logistic regression model is used for the hypothesis testing. The findings of the study indicate a positive and significant impact of audit committee characteristics, except audit independency which represents a negative association, and changes of auditor on financial restatement. The innovation of the present study relative to other conducted studies lies in the simultaneous evaluation of audit committee characteristics and change of auditor on the quality of financial reporting. Such results could be appropriate for Stocks and Securities practitioners to comply with the chart of the audit committee, to necessitate the use of corporate governance principles, and to voluntarily provide a corporate governance report.
Keywords: M42; M48; M41; 330; financial reporting quality; audit committee characteristics; financial restatement